Differences in dose-effect curves for UV-induced reverse mutations at two different loci - C. Auerbach; B. J. Kilbey; G. Kolmark (Fungal Genetics Reports, 1962)
Differences in dose-effect curves for UV-induced reverse mutations at two different loci